Tuning adatom mobility and nanoscale segregation by twin formation and polytypism. (5th December 2018) - Francaviglia, Luca; Tütüncüoglu, Gözde; Matteini, Federico; Morral, Anna Fontcuberta i
Abstract: Nanoscale variations in the composition of an Al x Ga1− x As shell around a GaAs nanowire affect the nanowire functionality and can lead to the formation of localized quantum emitters. These composition fluctuations can be the consequence of variations of crystal phase and/or nanoscale adatom mobility. By applying electron-microscopy-related techniques we correlate the optical, compositional and structural properties at the nanoscale on the same object. The results indicate a clear correlation between the twin density in the nanowire and the quantum-emitter density as well as a significant redshift in the emission. We propose that twinning increases nanoscale segregation effects in ternary alloys. An additional redshift in the emission can be explained by the staggered band alignment between wurtzite and zinc-blende phases. This work opens new avenues in the achievement of homogeneous ternary and quaternary alloys in nanowires and in the engineering of the segregation effects at the nanoscale.